2000
DOI: 10.1017/s0022149x00000111
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Echinococcus granulosus in Arbil province, northern Iraq, 1990–1998

Abstract: During the period 1990–1998, 99 cases of human cystic hydatidosis (12.4 cases per year) were surgically treated at the two main hospitals in Arbil province, northern Iraq, and from this the human occurence for the province was estimated to be 2 per 100,000 inhabitants. In the same area, 1270 sheep, 550 goats and 320 cattle were examined at slaughter for hydatid cysts and prevalence rates were found to be 15.0%, 6.2% and 10.9%, respectively. A decreasing tendency in livestock prevalences was found towards the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
48
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 11 publications
22
48
7
Order By: Relevance
“…The fertility rate of hydatid cysts in sheep reported in the literature varies in different regions of the world. Cyst fertility rates in sheep were reported as 84% in Saudi Arabia (Farah, 1987), 90% in India (Singh and Dhar, 1988), 7.6% in Sardinia (Bortoletti et al, 1990), 51% in Greece (Himonas et al, 1994), 38.1% in Jordan (Kamhawi et al, 1995) and 64% in Iraq (Saeed et al, 2000). The cyst fertility rate in sheep of the Kirikkale region was similar to that known from previous studies reported in Turkey as 61.2% (Senlik, 2000) and 93% (Guralp and Dogru, 1971).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The fertility rate of hydatid cysts in sheep reported in the literature varies in different regions of the world. Cyst fertility rates in sheep were reported as 84% in Saudi Arabia (Farah, 1987), 90% in India (Singh and Dhar, 1988), 7.6% in Sardinia (Bortoletti et al, 1990), 51% in Greece (Himonas et al, 1994), 38.1% in Jordan (Kamhawi et al, 1995) and 64% in Iraq (Saeed et al, 2000). The cyst fertility rate in sheep of the Kirikkale region was similar to that known from previous studies reported in Turkey as 61.2% (Senlik, 2000) and 93% (Guralp and Dogru, 1971).…”
Section: Discussionsupporting
confidence: 86%
“…The fertility of hydatid cysts varies depending on intermediate host species and geographical areas (Abdel-Hafez et al, 1986;Farah, 1987;Gusbi et al, 1987;Irshadullah et al, 1989;Bortoletti et al, 1990;Himonas et al, 1994;Kamhawi et al, 1995;Saeed et al, 2000).…”
Section: Acta Veterinaria Hungarica 51 2003mentioning
confidence: 99%
“…In a study by Scala et al that to do in Italy in 2006 the prevalence rate of hydatid cyst 75% reported [22]. Also Saeed et al during the period 1990-1998, 1270 sheep, 550 goats and 320 cattle were examined at slaughter for hydatid cysts and prevalence rates were found to be 15.0%, 6.2% and 10.9%, respectively [23]. In the Scala and Saeed studies like our study, the highest frequency of cysts was in sheep.…”
Section: Discussionmentioning
confidence: 97%
“…In Rostami Nejad et al study 7.13% lungs and 7.13% livers and 3.95% peritoneal cavity were contaminated by hydatid cyst [7]. In Saeed et al study between 63% and 82% livers and between 72% and 79% lungs were contaminated [23]. Molan in his study that performed on sheep, liver with 6.5% and lung with 3.8 were infected [24].…”
Section: Discussionmentioning
confidence: 99%
“…Hydatid disease is most extensively found in East and North Africa, India, Australia, New Zealand, South America, and Middle East including Iran [1][2][3][4][5][6][7][8][9]. Mostly the rate of the infection in carnivores such as dog and herbivores such as sheep, camels are significant but humans also get the infections accidentally [10][11][12][13][14][15][16], hereby, hydatidosis is a major health-economic problem, that has become one of the WHO`s active plans for controlling the disease [17].…”
Section: Introductionmentioning
confidence: 99%